Mapping of human arm impedance characteristics in spatial movements - Tasnuva Tabashhum Choudhury; Md Mozasser Rahman; Md Raisuddin Khan; Fazlur Rashid; Md. Rabiul Islam Sarker (Institute of Advanced Engineering and Science, 2022)
In this paper, impedance characteristics are determined for discrete movement. It explores the changes in impedance characteristics of human arm during a complete task. This study considered 3D spatial movement for horizontal adduction and abduction. The human arm is considered as mass-spring-damper system and the modelling is done accordingly. The model is solved for 3 degree of freedom (3DoF) spatial movement usually used for daily work. Inertia, stiffness and damping factor are the impedance characteristics considered in the model. Using position measuring device, the position data of elbow and wrist were obtained with respect to pre-defined references. The data were used to calculate velocity, acceleration and force. Then, the impedance characteristics were determined by solving the equation of motion of the mass-spring-damper system corresponding to different position of the wrist on the trajectory. These impedance factors were then plotted to map the characteristics. The mappings were done for both total durations to complete task and for segments of the task. The impedance characteristics were observed to vary according to the movement of the arm. Significant changes of damping factor and stiffness were found to occur at the beginning and end of the arm movement.